Cochrane plain language summaries are highly heterogeneous with low adherence to the standards - Antonia Jelicic Kadic; Mahir Fidahic; Milan Vujcic; Frano Saric; Ivana Propadalo; Ivana Marelja; Svjetlana Dosenovic; Livia Puljak (BMC Medical Research Methodology, 2016)
Abstract Background The aim of this study was to analyze whether Cochrane plain language summaries (PLSs) adhere to the Standards for the reporting of Plain Language Summaries in new Cochrane Intervention Reviews (PLEACS). Methods A systematic analysis of adherence to the measurable PLEACS items was performed for Cochrane PLSs published from March 2013 to the end of January 2015. Duplicate independent data extraction was performed. An adherence score was calculated for each PLS and for the Cochrane Review Groups (CRGs) that published them. Results Of the 1738 analyzed PLSs, not a single one adhered fully to the measured PLEACS items. The highest adherence was found for absence of details of the search strategy (99 % adherence), and the lowest adherence for an item mandating to address quality according to the GRADE system (0.7 % adherence). Overall adherence percentage of PLSs reporting reviews with included studies was 57 %. Different CRGs had a wide range of adherence scores. Conclusions Cochrane plain language summaries are highly heterogeneous with a low adherence to the PLEACS standards. Therefore, there is much room for improving the content and consistency of the PLS. A standardization of PLSs is necessary to ensure delivery of proper and consistent information for consumers.